Influence of wastewater reuse on the microbiological quality of sunflowers for animal feed - Roseanne Santos de Carvalho; José Sebastião dos Santos Filho; Larissa Oliveira Gama de Santana; Danielle Almeida Gomes; Luciana Coêlho Mendonça; Gregório Guirado Faccioli (Revista Ambiente & Água, 2013)
The use of treated wastewater for agricultural purposes can be an alternative to maintaining the quality of water bodies and the biota of natural systems. It can also reduce the demand for water and preserve water supplies for more important uses. This study aimed to evaluate the effects of wastewater reuse in the microbiological quality of above ground parts of sunflower crops. The experiment was conducted from July to September 2012 in the greenhouse of the Department of Agricultural Engineering (DEA) at the Federal University of Sergipe, São Cristóvão Campus. Treated wastewater was collected at the Sewage Treatment Plant (WWTP) Rosa Elze, located in the municipality of São Cristóvão, SE. Irrigation was performed using different ratios of water and treated wastewater. The irrigation followed the FAO 56 method. We used a completely randomized design (CRD) with five treatments and four replicates per plot. The data were analyzed according to the parameters recommended by Resolution no. 12, 02/01/2001 of the Brazilian National Agency for Sanitary Vigilance. Coliforms, E. coli, yeast and mold, and Salmonella were counted. Results have shown that the microbiological quality of the superficial area of sunflower crops analyzed met the standards of Brazilian law. However, further studies should be conducted to investigate the effects of soil.